2006
DOI: 10.1097/01.wnr.0000221828.10846.ba
|View full text |Cite
|
Sign up to set email alerts
|

Phonetic mismatch negativity predicts verbal memory deficits in schizophrenia

Abstract: Deficits in auditory sensory memory at the electrophysiological level as indexed by mismatch negativity and those in auditory verbal memory at the neuropsychological level have been independently demonstrated in previous studies of schizophrenia. We predicted a specific association between these indices in schizophrenia. Mismatch negativities elicited by change in tone duration and phoneme duration were recorded in 23 schizophrenia patients, who were also evaluated for auditory verbal memory and executive func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 21 publications
1
36
1
Order By: Relevance
“…Stage 1 APS scores that were averaged across a range of auditory stimuli were further associated with executive functioning, whereas APS scores averaged across the entire hour of training (Hour 1 metrics) were also moderately associated with baseline verbal memory. These findings are consistent with previous research demonstrating relationships between auditory perception and performance in complex cognitive domains (Javitt, 2009; Kawakubo et al, 2006; Leitman et al, 2005; Light, Swerdlow, & Braff, 2007; Rissling et al, 2014). As evidenced by their moderate-to-strong associations with all cognitive domains, the composite metrics calculated after a full hour of training appear to provide a more robust indicator of auditory perceptual efficiency than do metrics derived from Level 1 or Stage 1.…”
Section: 1 Discussionsupporting
confidence: 93%
“…Stage 1 APS scores that were averaged across a range of auditory stimuli were further associated with executive functioning, whereas APS scores averaged across the entire hour of training (Hour 1 metrics) were also moderately associated with baseline verbal memory. These findings are consistent with previous research demonstrating relationships between auditory perception and performance in complex cognitive domains (Javitt, 2009; Kawakubo et al, 2006; Leitman et al, 2005; Light, Swerdlow, & Braff, 2007; Rissling et al, 2014). As evidenced by their moderate-to-strong associations with all cognitive domains, the composite metrics calculated after a full hour of training appear to provide a more robust indicator of auditory perceptual efficiency than do metrics derived from Level 1 or Stage 1.…”
Section: 1 Discussionsupporting
confidence: 93%
“…As previously mentioned, medication did not abolish MMN abnormality in schizophrenia patients (Catts et al, 1995;Kasai et al, 2002c ;Kawakubo et al, 2006;Korostenskaja et al, 2005;Umbricht et al, 1998Umbricht et al, , 1999. Furthermore, this abnormality was present irrespective of the inter-stimulus interval (ISI), the deviant-stimulus probability, and the magnitude of stimulus change .…”
Section: Mmn Amplitude Reduction In Schizophreniamentioning
confidence: 85%
“…This suggests that left-hemisphere structural planum-temporale abnormalities may underlie the functional abnormalities of fundamental language-related processing in schizophrenia patients. In addition, Kawakubo et al (2006) found that a MMN deficit with respect to the duration decrement of a speech sound (but not of a sinusoidal tone) was associated with poor auditory verbal memory in schizophrenia patients.…”
Section: Mmn Amplitude Reduction In Schizophreniamentioning
confidence: 98%
“…14 Neurophysiological measures of early auditory information processing (EAP) in schizophrenia correlate with both cognition 22–24 and functional outcome 25–28 , can be feasibly measured across diverse settings 29 , and thus have promising applications as endophenotypes in genomic studies and as biomarkers in clinical outcome studies. 14,29–36 …”
mentioning
confidence: 99%